Effect of storage time on histamine content in fish - O. Cenap Tekinşen; Suzan Yalçın; Mustafa Nizamlıoğlu (Eurasian Journal of Veterinary Sciences)
The study was carried out to determine the effect of sforage time on histamine content in fish. Mackerel, bonito and anchovy fish were usedin this study. Fish samples were stored at 4°C during 3 days. The concentrations of histamine in fish were determined by spectrofluorometer during 3 days of storage. The mean histamine levels for mackerel, bonito and anchovy fish after 3 days of sforage period were found as 6.28, 3. 70 and 3.25 ,µg/g, respectively. Based on this study, it is concluded that the histamine levels in mackerel, bonito and anchovy fish during sforage at 4°C even after 3 days were below toxic leve!.